2022
DOI: 10.1038/s41598-022-05042-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 behavioral health and quality of life

Abstract: In addition to concern about physical health consequences of COVID-19, many researchers also note the concerning impact on behavioral health and quality of life due to disruption. The purpose of this paper is to explore pathways of COVID-19 behavioral health and quality of life. We found increased anxiety, depression, and alcohol misuse and that the pandemic exacerbated prior problems. Further community indicators also lead to poorer behavioral health and overall decreased quality of life. The nature of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 82 publications
2
43
1
1
Order By: Relevance
“…The pandemic has shown that in times of acute threat of Covid, health care is the most important component of people's lives. The proportion of individuals who perceive the item 'staying healthy' as the most important (grade 5) has increased, which is consistent withHansel et al (2022). AsFedchenko & Danker (2015) state, physical and mental health is a prerequisite for the competitiveness of individuals in the labour market.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The pandemic has shown that in times of acute threat of Covid, health care is the most important component of people's lives. The proportion of individuals who perceive the item 'staying healthy' as the most important (grade 5) has increased, which is consistent withHansel et al (2022). AsFedchenko & Danker (2015) state, physical and mental health is a prerequisite for the competitiveness of individuals in the labour market.…”
supporting
confidence: 71%
“…Due to concerns about the future, households are trying to save, which works well for highincome households (MacGee et al, 2022) but is a problem for low-income households, which are often unable to pay their bills (Findling et al, 2021) and therefore incur debts (MacGee et al, 2022). In a pandemic, the quality of life for some individuals declines greatly, and they struggle just to stay healthy and meet basic human needs (Hansel et al, 2022). Changes in individuals' lives can affect their behaviour and competitiveness in the labour market, which Sabetova (2016) summarises as total abilities, competencies and motives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social distancing, self-isolation, and various restrictions that people faced in all around the world during the last 2.5 years affected mental health of people, particularly those in younger age (16). Recent studies have shown that both self-efficacy and quality of life declined significantly in individuals due to COVID-19 pandemic (17,18). Moreover, our study was conducted in a time frame where the highest COVID-19 cases were reported in Turkey (19).…”
Section: Discussionmentioning
confidence: 97%
“…Multiple and long-term disasters can negatively affect behavioral health, with the extensive literature noting the association among cumulative adversities and poor mental and physical health outcomes (Felitti, 2002;Shrira et al, 2010;Finkelhor et al, 2013;Lowe et al, 2013). Similar patterns of mental health concerns, for example, increased anxiety, depression, and decreased quality of life, are expected given the many hardships associated with the COVID-19 pandemic, a type of biological disaster (Osofsky et al, 2020;Hansel et al, 2022). It is urgent to use lessons learned from past disasters, such as Hurricane Katrina and the Deepwater Horizon (DWH) Gulf oil spill, to focus growth-based services following the many shared adversities due to the ongoing pandemic.…”
Section: Introductionmentioning
confidence: 98%